Virtual support groups for health problems: typology and representativeness by illness group - Suriá Martínez, Raquel; Beléndez Vázquez, Marina (Anales de Psicología / Annals of Psychology, 2010)
The number of internet discussion forums for health problems increased in recent years. However, the study about characteristics and typology of internet forums created for Spanish-speaking users is scarce. This study is aimed to examine the availability of health-related Internet forums by type of forum and by illness and to find out if a comparable pattern emerges when comparing with the availability of face-to-face support groups for these health problems. Nine hundred thirteen Internet forums and 249 face-to-face support groups for 20 health problems were located. Results showed differences in the number of Internet forums by type of forum and by health problem. We found more non moderated webforums than moderated ones. Obesity, AIDS, anorexia, anxiety and cancer were the health problems with more Internet forums. The same pattern was found when comparing with the number of existing face-to-face support groups for these health problems.